2020
DOI: 10.3389/fnagi.2020.582904
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Improves White Matter Perfusion and Integrity in Rat Model of Vascular Dementia: An MRI-Based Imaging Study

Abstract: White matter lesions induced by chronic cerebral hypoperfusion are associated with cognitive impairment in vascular dementia (VaD). Previous studies have shown that acupuncture can ameliorate the cognitive deficits of individuals with VaD. However, the neuroimaging mechanisms of acupuncture on white matter perfusion and integrity remain elusive. In this study, the VaD model was induced by bilateral common carotid arteries occlusion (BCCAO) in rats. Novel object recognition task and Morris water maze were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…With the deepening of animal studies, a large amount of evidences showed that acupuncture can effectively treat cognitive dysfunction in animals through multiple targets or pathways (Ye et al, 2017a ). Ma et al ( 2020 ) conducted an Magnetic Resonance Imaging (MRI)imaging-based acupuncture study, which found that the combination of GV20 + ST36 significantly attenuated the loss of myelin basic proteins and obviously reduced Interleukin-1β (IL-1β), Interleukin-6 (IL-6), and Ionized calcium bindingadaptor molecule-1 (Iba-1) by improving the perfusion and integrity of white matter. A quantitative proteomic study Isobaric Tags for Relative and Absolute Quantitation (iTRAQ) performed by Yang et al ( 2018a ) showed that most Differentially Expressed Proteins (DEPs) were associated with oxidative stress, apoptosis, and synaptic function, additionally, the proteins associated with acupuncture effects were also significantly involved in these three cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of animal studies, a large amount of evidences showed that acupuncture can effectively treat cognitive dysfunction in animals through multiple targets or pathways (Ye et al, 2017a ). Ma et al ( 2020 ) conducted an Magnetic Resonance Imaging (MRI)imaging-based acupuncture study, which found that the combination of GV20 + ST36 significantly attenuated the loss of myelin basic proteins and obviously reduced Interleukin-1β (IL-1β), Interleukin-6 (IL-6), and Ionized calcium bindingadaptor molecule-1 (Iba-1) by improving the perfusion and integrity of white matter. A quantitative proteomic study Isobaric Tags for Relative and Absolute Quantitation (iTRAQ) performed by Yang et al ( 2018a ) showed that most Differentially Expressed Proteins (DEPs) were associated with oxidative stress, apoptosis, and synaptic function, additionally, the proteins associated with acupuncture effects were also significantly involved in these three cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 40 Acupuncture at the Baihui (GV20) and Zusanli (ST36) points has been found to prevent cognitive function decline in rat models of vascular dementia by ameliorating white matter perfusion and maintaining its integrity. 47 In addition, acupuncture at the Yanglingquan (GB34) point was found to potentially enhance the communication between cortices with damaged white matter tracts in patients with ischemic stroke. 48 Therefore, we infer that acupuncture modulates these alterations of white matter, thereby preventing the development of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, improving the CBF is a promising therapeutic method for the treatment of white matter injury. Ma et al discovered that acupuncture increased the CBF, and preserved the myelin integrity without in uencing the axons in a rat model of vascular dementia [44]. In a clinic trial, EA treatment increased CBF and improved the outcome of SAH patients through alleviating vasospasm [7].…”
Section: Discussionmentioning
confidence: 99%